1977
DOI: 10.1136/thx.32.6.743
|View full text |Cite
|
Sign up to set email alerts
|

Delayed non-mycotic false aneurysm of ascending aortic cannulation site.

Abstract: . (1977). Thorax, 32,[743][744][745][746][747][748] Delayed non-mycotic false aneurysm of ascending aortic cannulation site. Two cases of delayed non-mycotic false aneurysm arising from the ascending aortic cannulation site, presenting one-and-a-half years and seven years after cardiopulmonary bypass, are described. These two cases represent an incidence of 0O12% of this complication. Repair using profound hypothermia and circulatory arrest with femoral artery and femoral vein cannulation for cardiopulmonary b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…1 Nonmycotic aneurysm of the ascending aorta at the previous aortic cannulation site is a rare but possibly fatal complication if it ruptures. 2 Flick et al reported the fi rst case of a saccular aneurysm at a previous aortic cannulation site in 1971, 3 since when many other cases have been reported, all of which were pseudoaneurysms. 1,3-5 Conversely, in our patient, the medial elastic fi brous tissue was thinning, but pathologic examination showed that its continuity was completely preserved all around the aneurysmal wall, contradicting the initial clinical diagnosis of a pseudoaneurysm.…”
Section: Discussionmentioning
confidence: 97%
“…1 Nonmycotic aneurysm of the ascending aorta at the previous aortic cannulation site is a rare but possibly fatal complication if it ruptures. 2 Flick et al reported the fi rst case of a saccular aneurysm at a previous aortic cannulation site in 1971, 3 since when many other cases have been reported, all of which were pseudoaneurysms. 1,3-5 Conversely, in our patient, the medial elastic fi brous tissue was thinning, but pathologic examination showed that its continuity was completely preserved all around the aneurysmal wall, contradicting the initial clinical diagnosis of a pseudoaneurysm.…”
Section: Discussionmentioning
confidence: 97%